Fuzzy-Like Multiple Objective Decision Making - Xu, Jiuping; Zhou, Xiaoyang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Decision makers usually face multiple, conflicting objectives and the complicated fuzzy-like environments in the real world. What are the fuzzy-like environments? How do we model the multiple objective decision making problems under fuzzy-like environments? How do you deal with these models? In order to answer these questions, this book provides an up-to-date methodology system for fuzzy-like multiple objective decision making, which includes modelling system, model analysis system, algorithm system and application system in structure optimization problem, selection problem, purchasing problem, inventory problem, logistics problem and so on. Researchers, practitioners and students in management science, operations research, information science, system science and engineering science will find this work a useful reference.
Part 1 Fuzzy Set Theory -- Part 2 Fuzzy Multiple Objective Decision Making -- Part 3 Fuzzy Random Multiple Objective Decision Making -- Part 4 Bifuzzy Multiple Objective Decision Making -- Part 5 Fuzzy Rough Multiple Objective Decision Making.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).